Semiconductor quantum dots for labeling glycoproteins on cell membrane - Low, Ren Fong. (2011)
In this report, quantum dots conjugated with 3-aminophenylboronic acids tag are used in imaging sialic acid moieties on the HePG2 hepatic cancer cells. Labeling of cancer cells are enabled due to the affinity of QDs probes towards the carbohydrate enriched coating or sialic acids that are overexpressed in most of the cancer cells. Thus, the expression of sialic acids on cell surfaces are of considerable interests, providing rational indexes of the dynamic changes in tumor malignancy, metastatic potential, diabetic symptoms, and other SA-associated biological events. Pretreatment of cancer cells is not required due to the high specificity and sensitivity of this QD probes. In addition, tagging is done in a short time which is an attractive feature of using this QD probes as fluorophores. It is found that sialic acids labeled with QD probes are distributed in a dappled manner after endocytosis in the perinuclear region. Advances in QD production and surface modification will result in the development of a new technology platform in the labeling and detection of glycans structures in the future.